Minga biographic workshops with highly skilled migrant women: enhancing spaces of inclusion - Riaño, Yvonne (My University, 2016)
This article proposes the notion of ‘marginalised elites’ to examine highly skilled migrant women, a group that has been neglected by feminist participatory research. It asks what principles and methods can be used towards inclusive practices in studies of migration and social exclusion. The paper contributes to the literature by designing and critically evaluating the method of Minga biographic workshops, which create inclusionary spaces of data collection and critical analysis with highly skilled migrant women living in Switzerland. Using this case study, the paper questions notions of privilege, power and positionality commonly used in feminist participatory approaches. Minga workshops enhance spaces of inclusion, become ‘spaces of personal transformation’, question the perceived inferiority of migrant women, and produce original scientific insights on social exclusion. These results point to the role of academics as facilitators of personal transformation, and the need to closely consider the added scientific value of feminist participatory methodologies.
Keywords: elites; feminist participatory methods; highly skilled migrants; migrant women; migration; biographic workshops; positionality; power; social exclusion; spaces of inclusion